Men's perspectives on male participation in antenatal care with their pregnant wives: a case of a military hospital in Lusaka, Zambia - Hamalambo Muloongo; Doreen Sitali; Joseph Mumba Zulu; Alice Ngoma Hazemba; Oliver Mweemba (BMC, 2019)
Abstract Background Male partner participation in antenatal care (ANC) is important and contributes to better maternal and neonatal birth outcomes. Studies have been conducted to explore male participation in ANC and barriers to participation. However, these studies have been conducted in the general population and not the military settings, which are gendered institutions. This study aimed to explore the perspectives of male participation in ANC in a military setting. Methods A qualitative case study approach using convenient sampling was used to enlist sixteen (n = 16) military men whose partners or wives were attending ANC. In-depth interviews were conducted with participants to get their perspectives on their participation in ANC. The interviews were transcribed verbatim and codes, categories and themes were generated from the data. Data analysis was done manually and was guided by thematic framework analysis approach. We designed a table which listed all emerging themes, categories and sub-themes. Results Participants were aged 27-45 years and some attained tertiary education. Five themes emerged to explain the perspectives of male participation in ANC. Men's roles were perceived to be limited to provision of appropriate food and supplies, physical and emotional support. Generally, ANC attendance was considered a woman's private activity because even health care providers were mostly female. However, the desire to have a healthy baby prompted many to seek information on ANC. On the other hand, priority given to couples attending ANC and the need to be part of the decision making motivated some to participate. For the participants in this study, military operations, fear of being tested for HIV and the belief that presence of men in ANC interferes with care made them shun the services. Conclusion Lack of awareness on the importance of male participation in ANC impacted on the understanding of access and use of services by participants. The study has practical implications in the military institution to formulate policy on male participation in ANC to improve maternal and newborn health outcomes as well as support staff who have to attend to their pregnant wives or partners.